Can Seismic Observations of Bed Conditions on Ice Streams Help Constrain Parameters in Ice Flow Models? - Kyrke-Smith, Teresa; Gudmundsson, Hilmar; Farrell, Patrick (Journal of Geophysical Research: Earth Surface, 2017)
We investigate correlations between seismically derived estimates of basal acoustic impedance and basal slipperiness values obtained from a surface‐to‐bed inversion using a Stokes ice flow model. Using high‐resolution measurements along several seismic profiles on Pine Island Glacier (PIG), we find no significant correlation at kilometer scale between acoustic impedance and either retrieved basal slipperiness or basal drag. However, there is a stronger correlation when comparing average values along the individual profiles. We hypothesize that the correlation appears at the length scales over which basal variations are important to large‐scale ice sheet flow. Although the seismic technique is sensitive to the material properties of the bed, at present there is no clear way of incorporating high‐resolution seismic measurements of bed properties on ice streams into ice flow models. We conclude that more theoretical work needs to be done before constraints on mechanical conditions at the ice‐bed interface from acoustic impedance measurements can be of direct use to ice sheet models.